Erik Jørgen Hansen, Danskernes Levekår - 1986 sammenholdt med 1976, København: Reitzels Forlag, 1986, 144 s., 98,00 kr.; Erik Jørgen Hansen (red.), Vor tids fattigdom, København: Hans Reitzels Forlag, 1986, 130 s., 130,00 kr. - Lauritzen, Peter (Politica, 1987)
-